RESPONSE OF THE N AND P CYCLES OF AN OLD GROWTH MONTANE FOREST IN ECUADOR TO EXPERIMENTAL LOW LEVEL N AND P AMENDMENTS - VALAREZO MANOSALVAS, CARLOS (2010)
Atmospheric nitrogen (N) and phosphorus (P) depositions are expected to increase in the tropics as a consequence of increasing human activities in the next decades. In the literature, it is frequently assumed that tropical montane forests are N-limited, while tropical lowland forests are P-limited. In a low-level N and P addition experiment, we determined the short-term response of N and P cycles in a north Andean montane forest on Palaeozoic shists and metasandstones at an elevation of 2100 m a.s.l. to increased N and P inputs. We evaluated experimental N, P and N + P additions (50 kg ha−1 yr−1 of N, 10 kg ha−1 yr−1 of P and 50 kg + 10 kg ha−1 yr−1 of N and P, respectively) and an untreated control in a fourfold replicated randomized block design. We collected litter leachate, mineral soil solution (0.15 and 0.30 m depths), throughfall and litterfall before the treatment began (August 2007) until 16 months after the first nutrient application (April 2009). Less than 10 and 1% of the applied N and P, respectively, leached below the organic layer which contained almost all roots and no significant leaching losses of N and P occurred to below 0.15 m mineral soil depth. Deposited N and P from the atmosphere in dry and wet form were retained in the canopy of the control treatment using a canopy budget model. Nitrogen and P retention by the canopy were reduced and N and P fluxes in throughfall and litterfall increased in their respective treatments. The increase in N and P fluxes in throughfall after fertilization was equivalent to 2.5% of the applied N and 2% of the applied P. The fluxes of N and P in litterfall were up to 15% and 3%, respectively, higher in the N and N + P than in the control treatments. We conclude that the expected elevated N and P deposition in the tropics will be retained in the ecosystem, at least in the short term and hence, N and P concentrations in stream water will not increase. Our results suggest that in the studied tropical montane forest ecosystem on Palaeozoic bedrock, N and P are co-limiting the growth of organisms in the canopy and organic layer.